2020
DOI: 10.3389/fonc.2019.01535
|View full text |Cite
|
Sign up to set email alerts
|

miR-20b-5p, TGFBR2, and E2F1 Form a Regulatory Loop to Participate in Epithelial to Mesenchymal Transition in Prostate Cancer

Abstract: The transcription factor E2F1 regulates the expression of the miR-20b-5p precursor and is involved in epithelial-to-mesenchymal transition (EMT). Transforming growth factor-β1 (TGF-β1) induces EMT in prostate cancer (PCa) by binding to TGF-beta receptor 2 (TGFBR2) to activate TGF-β signaling. However, the relationship between TGFBR2, E2F1, and miR-20b-5p in the modulation of EMT in PCa cells remains unknown. In this study, we found that the level of miR-20b-5p expression was significantly lower in PC3 and DU14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…Significantly higher TGFBR1 mRNA levels were found in breast cancer patients with poor prognosis and small tumors as loss of TGFBR2 mRNA was evidenced in primary breast tumors, but, curiously, higher levels of this gene were associated with better prognosis (39), which, added to in vivo and in vitro esophageal squamous cell carcinoma experiments, suggested that TGFBR2 overexpression induces cell cycle arrest and suppress cell growth (40). Furthermore, recent research in cancer cell lines suggested that some miRNAs, such as miR-133b and miR-20b-5p, can inhibit the epithelial-mesenchymal transition (EMT) induced by TGF-β1 by targeting, respectively, TGFBR1 and TGFBR2 genes (41,42). As elucidated by Fuziwara and cols.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly higher TGFBR1 mRNA levels were found in breast cancer patients with poor prognosis and small tumors as loss of TGFBR2 mRNA was evidenced in primary breast tumors, but, curiously, higher levels of this gene were associated with better prognosis (39), which, added to in vivo and in vitro esophageal squamous cell carcinoma experiments, suggested that TGFBR2 overexpression induces cell cycle arrest and suppress cell growth (40). Furthermore, recent research in cancer cell lines suggested that some miRNAs, such as miR-133b and miR-20b-5p, can inhibit the epithelial-mesenchymal transition (EMT) induced by TGF-β1 by targeting, respectively, TGFBR1 and TGFBR2 genes (41,42). As elucidated by Fuziwara and cols.…”
Section: Discussionmentioning
confidence: 99%
“…[ 31 ] MiR-151a-5p was significantly over-expressed in colorectal cancer [ 32 ] and lung cancer. [ 33 ] MiR-20b-5p played an significant role in prostate cancer(Pca), [ 34 ] lung cancer, [ 35 ] laryngeal squamous cell carcinoma, [ 36 ] renal cell carcinoma, [ 37 ] cancer stem cells, [ 38 ] and so on. Nevertheless, there were a few studies involving miR-363-3p in AML.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that induction of miR-106b plays a crucial role in the suppression of the proliferation of prostate cancer cells in a process that involves the TGF-beta signaling pathway ( Zhang et al, 2012 ). Additionally, in human prostate cancer, miR-20b targets and downregulates TGFBR2, which in turn affects Smad2 activation and E2F1 expression, dysregulating the miR-20b-5p expression and contributing to TGF-β-induced epithelial-to-mesenchymal transition ( Qi et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%